Gambaran Pengelolaan Limbah Masker Sekali Pakai oleh Rumah Tangga pada Masyarakat di Kota Semarang - Lubriyana, Triyani; Nurjazuli, Nurjazuli; Dewanti, Nikie Astorina Yunita (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
The production of mask waste in the public of Semarang city reaches 1.2 kg per day. Mask waste is an infectious waste that requires proper management. The purpose of this study was to determine the knowledge, accessibility of information, and the practice of managing the waste of disposable masks by households in the community of Semarang city. This study is an observational analytic study with a cross-sectional design. Data collected using an online questionnaire survey. The sample in this study was 130 respondents aged 15-64 years who resided and domiciled in Semarang city. Data analysis used univariate and bivariate analysis with chi-square test statistical test. In this study, the results of univariate analysis were obtained, namely the majority of respondents had good knowledge of 52.3% of respondents, good information accessibility of 66.9% of respondents, and good practice of 54.6% of respondents. The results of the bivariate analysis showed that there was a relationship between knowledge and practice of respondents regarding household disposable waste management (p-value = 0.002) and there was no relationship between information accessibility and respondents practices regarding household mask waste management (p-value = 0.352). The conclusion of this study is the public of Semarang city already having knowledge, accessibility of information and good practices regarding how to manage single-use mask waste in households. The ease of accessing information that is already owned by the community does not affect the practice of managing waste masks which has been done.